2023
DOI: 10.3390/metabo13040511
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Mediated Control of Metabolites and Other Physiological Responses in Water-Stressed Leptocohloa fusca

Abstract: We investigated biochar-induced drought tolerance in Leptocohloa fusca (Kallar grass) by exploring the plant defense system at physiological level. L. fusca plants were exposed to drought stress (100%, 70%, and 30% field capacity), and biochar (BC), as an organic soil amendment was applied in two concentrations (15 and 30 mg kg−1 soil) to induce drought tolerance. Our results demonstrated that drought restricted the growth of L. fusca by inhibiting shoot and root (fresh and dry) weight, total chlorophyll conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 111 publications
(220 reference statements)
0
2
0
Order By: Relevance
“…With limitations to N-containing nutrients the over-accumulation of Cl − and excessive production of MG indicates the complex role of sugars in salt-sensitive P. divisum plants. Some previous studies on different plants, such as Hordeum vulagre L. [57], Solanum lcopersicum [46], Triticum aestivum L. [58], Corchorus olitorius [59], and Leptocohloa fusca [60], studied the MG-induced oxidative stress and its detoxification mechanisms under salinity and drought stress, respectively. However, to the best of our knowledge no studies were found on the exogenous Co and Ti applicationalleviating MG-induced oxidative stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…With limitations to N-containing nutrients the over-accumulation of Cl − and excessive production of MG indicates the complex role of sugars in salt-sensitive P. divisum plants. Some previous studies on different plants, such as Hordeum vulagre L. [57], Solanum lcopersicum [46], Triticum aestivum L. [58], Corchorus olitorius [59], and Leptocohloa fusca [60], studied the MG-induced oxidative stress and its detoxification mechanisms under salinity and drought stress, respectively. However, to the best of our knowledge no studies were found on the exogenous Co and Ti applicationalleviating MG-induced oxidative stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive N application would make the soil water consumption of dryland wheat too high before jointing, and the soil water storage in shallow and middle layers was insufficient, which would affect the sowing of wheat after jointing and lead to yield reduction [ 17 ]. The relationship between precipitation and yield in the Weibei drought source is shown in Figure 1 , and it is also presented that by using rainfall in the fallow period to predict yield and guide nitrogen application could reduce N by N180 kg ha −1 and ensure stable yield.…”
Section: Introductionmentioning
confidence: 99%